Is computer navigation when used in the surgery of iliosacral pelvic bone tumours safer for the patient?. (February 2017) - Laitinen, M. K.; Parry, M. C.; Albergo, J. I.; Grimer, R. J.; Jeys, L. M.
Abstract : Aims: Due to the complex anatomy of the pelvis, limb-sparing resections of pelvic tumours achieving adequate surgical margins, can often be difficult. The advent of computer navigation has improved the precision of resection of these lesions, though there is little evidence comparing resection with or without the assistance of navigation. Our aim was to evaluate the efficacy of navigation-assisted surgery for the resection of pelvic bone tumours involving the posterior ilium and sacrum. Patients and Methods: Using our prospectively updated institutional database, we conducted a retrospective case control study of 21 patients who underwent resection of the posterior ilium and sacrum, for the treatment of a primary sarcoma of bone, between 1987 and 2015. The resection was performed with the assistance of navigation in nine patients and without navigation in 12. We assessed the accuracy of navigation-assisted surgery, as defined by the surgical margin and how this affects the rate of local recurrence, the disease-free survival and the effects on peri-and post-operative morbidity. Results: The mean age of the patients was 36.4 years (15 to 66). The mean size of the tumour was 10.9 cm. In the navigation-assisted group, the margin was wide in two patients (16.7%), marginal in six (66.7%) and wide-contaminated in one (11.1%) with no intralesional margin. In the non-navigated-assisted group; the margin was wide in two patients (16.7%), marginal in five (41.7%), intralesional in three (25.0%) and wide-contaminated in two (16.7%). Local recurrence occurred in two patients in the navigation-assisted group (22.2%) and six in the non-navigation-assisted group (50.0%). The disease-free survival was significantly better when operated with navigation-assistance (p = 0.048). The blood loss and operating time were less in the navigated-assisted group, as was the risk of a foot drop post-operatively. Conclusion: The introduction of navigation-assisted surgery for the resection of tumours of the posterior ilium and sacrum has increased the safety for the patients and allows for a better oncological outcome. Cite this article: Bone Joint J 2017;99-B:261–6.